Chinese Policies Towards Warm Waters and Baloch Militancy - Asmat Naseem; Manzoor Khan Afridi, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
China is an evolving economic power, yet despite governing a large portion of the global land, it lacks access to warm waters that can be used throughout the year. China's desire to play an important role in the Indian Ocean stems from the country's historical ties to the region, as well as the presence of vital sea trade routes in the region. It has long-term economic and political-strategic interests in the Indian Ocean. The China-Pakistan Economic Corridor (CPEC) project aims to connect Pakistan and China through highways, oil and gas pipelines, railways, and an optical fiber link stretching from Gwadar to Xinjiang. The project, which is the largest in China-Pakistan bilateral relations, is beset by challenges. In the evolving regional dynamics, Balochistan as an energy and trade corridor could strengthen China-Pakistan relations and provide opportunities for shared benefits. However, a number of external powers are involved, and they are playing a role in fueling unrest in Balochistan, which is a stumbling block in China's policies toward warm waters.